Synoptic Spatio-Temporal Variability of the Photosynthetic Productivity of Microphytobenthos and Phytoplankton in a Tidal Estuary - Frankenbach, Silja; Ezequiel, João; Plecha, Sandra; Goessling, Johannes W.; Vaz, Leandro; Kühl, Michael; Dias, João Miguel; Vaz, Nuno; Serôdio, João (Frontiers in Marine Science, 2020)
Tidal estuaries are regarded as highly important ecosystems, mostly due to their high primary productivity and associated role as carbon sinks. In these ecosystems, primary productivity is mainly due to the photosynthetic carbon fixation by phytoplankton and microphytobenthos. The productivity of the two communities has been mostly studied separately, and directly comparable estimates of their carbon fixation rates in the same estuary are relatively scarce. The present study aimed to characterize the spatio-temporal variability of the productivity of phytoplankton and microphytobenthos in a tidal estuary, the Ria de Aveiro (Portugal), and to estimate the annual ecosystem-level budget for carbon fixation by the two communities. Productivity rates were determined based on synoptic in situ measurements of absolute rates of electron transport rate of photosystem II, using PAM fluorometry. Chlorophyll fluorescence indices were accompanied by measurements of salinity, temperature, water turbidity, solar irradiance, and planktonic and benthic microalgal biomass. Measurements were carried out hourly, along four spring-neap tidal cycles distributed along one year, on three sites of the estuary. The most pronounced trends in the spatio-temporal variability of the photophysiology and productivity of the two communities were the following: (i) maximum biomass and productivity were reached later for microphytobenthos (summer-autumn) than for phytoplankton (spring-summer); (ii) the absorption cross-section of PSII was generally higher for phytoplankton; (iii) the two groups showed a similar photoacclimation state, but microphytobenthos appeared as high light-acclimated when compared to phytoplankton. Biomass-specific productivity was on average higher for phytoplankton than for microphytobenthos, averaging 68.0 and 19.1 mg C mg Chl a-1 d-1, respectively. However, areal depth-integrated production rates were generally higher for the microphytobenthos than for the phytoplankton, averaging 264.5 and 140.0 mg C m-2 d-1, respectively. On an annual basis, phytoplankton productivity averaged 49.9 g C m-2 yr-1 while the productivity of microphytobenthos averaged 105.2 g C m-2 yr-1. When upscaling to the whole estuary, annual primary production rates of phytoplankton and microphytobenthos reached 4894.3 and 7534.0 t C yr-1, respectively, representing 39.4% and 60.6% of the combined total of 12428.3 t C yr-1 determined for the two communities in the Ria de Aveiro.